Genomic epidemiology of domestic and travel-associated Vibrio parahaemolyticus infections in the UK, 2008–2018. (September 2020) - Baker-Austin, Craig; Jenkins, Claire; Dadzie, Jerome; Mestanza, Orson; Delgado, Erick; Powell, Andy; Bean, Tim; Martinez-Urtaza, Jaime
Abstract: Globally, V. parahaemolyticus is the most prevalent food-poisoning bacterium associated with seafood consumption. To date, the epidemiology of Vibrio parahaemolyticus infections in the UK has remained unexplored. Here we analysed archived V. parahaemolyticus strains isolated from domestic infections and travellers into the UK from 2008 to 2018 and who had submitted clinical samples to Public Health England (PHE)'s Gastrointestinal Bacteria Reference Unit. A total of 48 strains were retrieved from the PHE strain collection, confirmatory tested by PCR and analysed by genome-wide phylogeny using a global collection of genomes with representative strains from the major epidemic clones. Most reported infections entering the UK originated from travellers returning from Southeast Asia, however cases were also reported to have potentially originated from the USA, Cuba, India, Turkey, Caribbean, France, Slovenia and also within the UK, highlighting the wide geographical spread of infections. A large genetic diversity of V. parahaemolyticus strains was observed, with sequence type 3 (ST3; pandemic group) strains the most common sequence type (23 of the 48 analysed strains, 47.9%). The majority of strains were tdh positive (25/48, 71%), with 5 isolates positive for both haemolysin genes ( tdh and trh ), with 2 isolates trh positive only (5.7%). Six isolates did not possess either haemolysin gene. We demonstrate that whole genome sequencing can be effective to type certain human pathogens entering a traditionally considered "non-endemic" county and this was captured via passive epidemiological surveillance systems. Such approaches may potentially provide a useful snapshot of the diversity of a given pathogen group circulating worldwide. Highlights: Little data is currently available on pathogenic Vibrio in non-endemic regions. This study provides insights of Vibrio parhaemolyticus strains entering the UK. Pandemic isolates (sequence type 3) predominate cases entering back into the UK. A number of novel and new sequence types were also identified from this study. Study outlines the use of passive surveillance for studying foodborne pathogens.